Results of the European survey on the assessment of deep molecular response in chronic phase CML patients during tyrosine kinase inhibitor therapy (EUREKA registry) - Möbius, Susanne; Schenk, Thomas; Himsel, Danny; Maier, Jacqueline; Franke, Georg-Nikolaus; Saussele, Susanne; Pott, Christiane; Andrikovics, Hajnalka; Meggyesi, Nora; Machova-Polakova, Katerina; Zizkova, Hana; Jurcek, Tomáš; et al. (Journal of cancer research and clinical oncology, 2019)
PURPOSE: The advent of tyrosine kinase inhibitor (TKI) therapies has revolutionized the treatment of chronic myeloid leukemia (CML). The European LeukemiaNet (ELN) recommends quantification of BCR-ABL1 transcripts by real-time quantitative PCR every 3 months during TKI treatment. Since a proportion of patients in deep molecular response (DMR: MR4, MR4.5, MR5) maintain remission after treatment stop, assessment of DMR is crucial. However, systematically collected molecular data, monitored with sensitive standardized assays, are not available outside clinical trials. METHODS: Data were collected on the standardized assessment of molecular response in the context of real-life practice. BCR-ABL1 transcript levels after > 2 years of TKI therapy were evaluated for DMR by local laboratories as well as standardized EUTOS laboratories. Since standardized molecular monitoring is a prerequisite for treatment discontinuation, central surveillance of the performance of the participating laboratories was carried out. RESULTS: Between 2014 and 2017, 3377 peripheral blood samples from 1117 CML patients were shipped to 11 standardized reference laboratories in six European countries. BCR-ABL1 transcript types were b3a2 (41.63%), b2a2 (29.99%), b2a2/b3a2 (3.58%) and atypical (0.54%). For 23.72% of the patients, the initial transcript type had not been reported. Response levels (EUTOS laboratory) were: no MMR, n = 197 (6.51%); MMR, n = 496 (16.40%); MR4, n = 685 (22.64%); MR4.5, n = 937 (30.98%); MR5, n = 710 (23.47%). With a Cohen's kappa coefficient of 0.708, a substantial agreement between EUTOS-certified and local laboratories was shown. CONCLUSIONS: Multicenter DMR assessment is feasible in the context of real-life clinical practice in Europe. Information on the BCR-ABL1 transcript type at diagnosis is crucial to accurately monitor patients' molecular response during or after TKI therapy.
Keywords: Young Adult; Treatment-free remission; Deep molecular remission; Standardization; kohortové studie; chronická fáze myeloidní leukemie; mladý dospělý; Cohort Studies; chronická myeloidní leukemie; CML; TFR; Europe; Adult; Aged; dospělí; senioři; registrace; inhibitory proteinkinas; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Leukemia, Myeloid, Chronic-Phase; Evropa; senioři nad 80 let; lidé; Eureka; Humans; Chronic myeloid leukemia; Molecular monitoring; Protein Kinase Inhibitors; Aged, 80 and over; BCR–ABL; laboratoře; Laboratories; Registries; lidé středního věku; Middle Aged